FORMATION AND COMPOSITION OF CEMENTED LAYERS IN LOW-SULPHIDE MINE TAILINGS, LAVER, NORTHERN SWEDEN - Alakangas L.; Öhlander B. (My University, 2006)
Cemented layers (hardpans) are common in carbonate or sulphide-rich mine tailings and where pyrrhotite is the predominating Fe-sulphide. Laver, northern Sweden, is an abandoned Cu-mine where the tailings have low pyrrhotite content, almost no pyrite and no carbonates. Two cemented layers at different locations in the Laver tailings impoundment were investigated, with the aim to determine their effects on metal mobility. The cementing agents were mainly jarosite and Fe-oxyhydroxides in the layer formed where the tailings have a barren surface, whereas only Fe-oxyhydroxides were identified below grass-covered tailings surface. Arsenic was enriched in both layers which also exhibit high concentrations of Mo, V, Hg and Pb compared to unoxidised tailings. Sequential extraction indicates that these metals and As were mainly retained with crystalline Fe-oxides, and therefore potentially will be remobilised if the oxic conditions become more reducing, for instance as a result of remediation of the tailings impoundment.
Keywords: HARDPAN; CEMENTING LAYER; METAL MOBILITY; NORTHERN SWEDEN; NORRBOTTEN; LAVER